2014
DOI: 10.1093/jxb/eru486
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression and alternative splicing between diploid and tetraploid watermelon

Abstract: The exploitation of synthetic polyploids for producing seedless fruits is well known in watermelon. Tetraploid progenitors of triploid watermelon plants, compared with their diploid counterparts, exhibit wide phenotypic differences. Although many factors modulate alternative splicing (AS) in plants, the effects of autopolyploidization on AS are still unknown. In this study, we used tissues of leaf, stem, and fruit of diploid and tetraploid sweet watermelon to understand changes in gene expression and the occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 74 publications
0
48
0
1
Order By: Relevance
“…Moreover, polyploids have been reported to affect the gene expression at the transcription level compared with diploids. For example, studies in watermelon have shown that 5,362 and 1,288 genes were up- and down-regulated, respectively, in autotetraploid compared with diploid watermelon46. So further studies are required to reveal the reason for tetraploid formation and the effect on gene expression after genome duplication event in S. psammophila .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, polyploids have been reported to affect the gene expression at the transcription level compared with diploids. For example, studies in watermelon have shown that 5,362 and 1,288 genes were up- and down-regulated, respectively, in autotetraploid compared with diploid watermelon46. So further studies are required to reveal the reason for tetraploid formation and the effect on gene expression after genome duplication event in S. psammophila .…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq technology has been applied to different model as well as non-model organisms for a variety of studies covering allele specific gene expression, new splice variants (Saminathan et al 2015), fusion transcript variants (Norton et al 2013;Ma et al 2014), quantitative trait loci regions (Lionikas et al 2012) and tissue specific putative biomarkers (Metsalu et al 2014). We believe that there may be enhanced expression of those early-phase response genes, which may trigger signaling events that would prepare the lung tissue of tolerant animals to undergo changes that help fight or protect against or else repair the injury caused due to hypobaric hypoxia exposure, while gene expression pattern in lungs of susceptible rats might indicate an opposite pattern.…”
Section: Lung Transcriptome Analysis and Mining Early-phase Response mentioning
confidence: 99%
“…This study acknowledged the tendency to increase for the amounts of polyploid cells in plant if it is treated with NPs. There are lots of researches proclaiming that increase in ploidy leads to improvements in economically valued plants attributes, for example, biomass increase and stress tolerance escalation [28][29][30][31]. The mitotic indexes obtained from rucola cells of untreated plants and from plants treated with nanoparticles are presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%